The politico-media complex confluence in Brazil: the political concentration in the media and its effect on the journalistic work - Rebouças, Bruno H.B. (Estudios sobre el Mensaje Periodístico, 2019)
This paper aims to analyze the relations established between the main media corporations and the political representatives in Brazil, focusing on three states of the Brazilian northeast: Bahia, Ceará and Rio Grande do Norte. Our main purpose is to analyze the structure of the infocommunications groups demonstrating the point of convergence between the media and the political systems in these states, their multiple concentration, and how the politico-media complex confluent structure affects journalism as a profession, in order to comprehend the political influence in the media and in the professional conduct, and the dependence on public funds and the political context. Also, to analyze and understand through a questionnaire and in-depth interviews with journalists, the perception on the informational plurality in those states, as well as addressing the issue of professional precariousness and the reasons behind it.
Keywords: Media; politics; oligopoly; politico-media confluence; infocommunications